Immunosuppressive Therapy After Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis Patients—High Efficacy of Rituximab - Gernert, Michael; Tony, Hans-Peter; Fröhlich, Matthias; Schwaneck, Eva Christina; Schmalzing, Marc (Frontiers in Immunology, 2022)
Background: Systemic sclerosis (SSc) patients often need immunosuppressive medication (IS) for disease control. If SSc is progressive despite IS, autologous hematopoietic stem cell transplantation (aHSCT) is a treatment option for selected SSc patients. aHSCT is effective with good available evidence, but not all patients achieve a treatment-free remission after aHSCT. Thus far, data about the need of IS after aHSCT in SSc is not published. The aim of this study was to investigate the use of IS after aHSCT, its efficacy and the occurrence of severe adverse events (SAEs). Methods: 27 Patients with SSc, who had undergone aHSCT were included in this single-center retrospective cohort study. Clinical data, including IS, SAEs and lung function data was collected. Results: 16 of 27 (59.3%) patients received IS after aHSCT. Methotrexate, rituximab, mycophenolate, cyclophosphamide, and hydroxychloroquine were most commonly used. Main reason for starting IS was SSc progress. Nine patients received rituximab after aHSCT and showed an improvement in modified Rodnan skin score and a stabilization of lung function two years after rituximab. SAEs in patients with IS after aHSCT (50.0%) were not more common than in patients without IS (54.6%). SAEs were mostly due to SSc progress, secondary autoimmune diseases or infections. Two deaths after aHSCT were transplantation-related and three during long-term follow up due to pulmonary arterial hypertension. Conclusion: Disease progression and secondary autoimmune diseases may necessitate IS after aHSCT in SSc. Rituximab seems to be an efficacious treatment option in this setting. Long-term data on the safety of aHSCT is reassuring.